Advances in electrocatalytic urea synthesis: From fundamentals to applications - Zhenlin Mo; Jincheng Mu; Baojun Liu (Advanced Powder Materials)
The electrocatalytic synthesis of urea (ESU) is a green and sustainable alternative to conventional production methods, and the related research is still in its infancy. Up to now, the field has been explored by several reviews, however, the authors are focusing on some particular problems and could not provide a holistic view of the ESU. Based on these considerations, the novelty of this review lies in its comprehensive and systematic framework, as well as its in-depth analysis and general summary of several key issues. Hence, in this review, we critically evaluated the ESU through in-depth studies of various aspects, including nitrogen sources, catalysts choice, conditions modifications, detection methods, product calculations, and mechanisms evaluation, etc. In addition, after analyzing the reaction routes, reaction kinetics/thermodynamics and techno-economics assessment are also investigated. Finally, the summary and outlook are presented eventually, providing valuable insights for the related research. We believe that we will provide researchers with a comprehensive and clear picture of green synthesized urea, which is of great academic and practical significance.